When Green Goes Dark: Peter Weir’s Mosquito Coast as Eco-Dystopia - Mundler-Arantes, Helen E. (International Transitions, 2026)
his article explores the deployment of Peter Weir’s 1986 film The Mosquito Coast, an adaptation of Paul Theroux’s 1981 novel, as a learning object for first-year undergraduates in Green Business at AEI-International School, UPEC. Allie Fox, a brilliant inventor, but with a tenuous grasp on sanity, moves his family from a comfortable life in Massachusetts to an abandoned rainforest settlement in Honduras, where he sets up an eco-utopia, including a supposedly “green” business. The slide into dystopia which inevitably follows, is analysed through the lenses of Timothy Morton’s concept of dark ecology, and and a modified version of Michael E. Zimmerman’s eco-fascism. This article reflects on how this film can be used to help students abandon a naïve view of green business as salvation, and to explore the nuances of human enmeshment in nature.